Development of Dam-Daman Learning Media on Flat Shape Material to Improve Learning Outcomes of Class III Elementary Schools in Tasikmalaya - Mohammad Arfan Munajat; Mohammad Fahmi Nugraha; Yopa Taufik Saleh (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to develop a dam-daman learning media on flat shape material to improve learning outcomes for third grade elementary school students in Tasikmalaya. Aims to find out how the development of dam-daman learning media on flat material and determine the effectiveness of dam-daman learning media on flat material. The method used is the RD (Research and Development) Borg and Gall method with seven stages. The sample used was simple random sampling technique from the entire population of 4 elementary schools and the samples in this study were class III students consisting of 6 students at SDN Sindangsari INP as a small group trial, 12 students at SDN Condong as a large group trial. and 27 students as an effectiveness test at SDN 2 Cileuleus. Instruments for collecting data by observation, interviews and validation instrument questionnaires (validation of media, language, material and questions). Quantitative and qualitative data analysis techniques from the results of the feasibility and effectiveness tests. Based on the results of the research, we have obtained a dam-daman learning media on flat shape material. This dam-daman learning media for elementary school students of class III flat shapes has very good criteria in terms of media, language, material and student responses. Based on the feasibility test by experts and student responses in the form of scores, where the validation results of media experts got a score of 3.63, linguists at 4.00, material experts at 4.00 and student responses at 3.55. Then the results of the effectiveness test in the control class got an N-Gain score of 0.1 with low criteria and the results of the control class got a score of 0.7 with high criteria. Therefore using dam-daman media can certainly improve student learning outcomes. However, this is inseparable from the need for further research because this study tested the effectiveness of an elementary school in the Cisayong sub-district.